Nanostructured starch combined with hydroxytyrosol in poly(vinyl alcohol) based ternary films as active packaging system. (1st August 2018) - Luzi, Francesca; Fortunati, Elena; Di Michele, Alessandro; Pannucci, Elisa; Botticella, Ermelinda; Santi, Luca; Kenny, José Maria; Torre, Luigi; Bernini, Roberta
Graphical abstract: Highlights: Nanostructured starch was obtained by acid hydrolysis and ultrasound irradiation. Starch granules characterized by 33% or 75% wt. of amylase content were selected. Nanostructured starch was combined with hydroxytyrosol in cast PVA films. Nanostructured starch was able to tune the release of hydroxytyrosol in 21 days. Low amylose starch nanoparticles have better antioxidant capacity in ternary films. Abstract: Novel ternary films have been realized by using poly(vinyl alcohol) (PVA) as polymeric matrix, nanostructured starch as reinforcement phase and hydroxytyrosol (HTyr), a low-molecular phenolic compound present in olive oil, as antioxidant agent. Nanostructured starch, in the form of starch nanocrystals (NC) and nanoparticles (NP) obtained by acid hydrolysis and ultrasound irradiation of starch derived from the bread wheat variety Cadenza (WT, amylose content 33%) and a derived-high amylose line (HA, amylose content 75%), was considered. The developed multifunctional films were characterized in terms of morphological, thermal and optical properties, water absorption capacity, overall and specific migration into a food simulant and antioxidant properties. Experimental data showed a prolonged release of HTyr from all ternary films and the released HTyr retained a strong antioxidant activity. The data, compared to those of PVA/HTyr binary films, demonstrated the key role of nanostructured starch in the ternary formulations in promoting a gradual release of HTyr. Overall, PVA fillm combined with nanoparticles from low amylose starch and hydroxytyrosol resulted as the most promising ternary formulation for food packaging applications.